Online Loan Fraud Cases in Indonesia: Diamond Fraud Dimensions - Junaidi, Junaidi; Endraria, Endraria (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this paper is to show fraud under the guise of online loans that harm the community and provide solutions so that people avoid these scams. In the Online Loan program, many people have complained about the dissemination of personal data to the authorities that have been carried out by the Online Loan organizer without prior notification from the party concerned. The use of data used in this paper comes from journal articles and also online news related to fraud cases under the guise of online loans that occur in Indonesia. The main factor in the rise of illegal online loans (Pinjol) is the unfulfilled needs and strong belief in money. The Financial Services Authority (OJK) said that the level of financial literacy and inclusion in the peer-to-peer financial technology (fintech P2P) technology industry or online loans (pinjol) is still relatively low. The results stated that it is necessary to implement stricter regulations, increase transparency, build a centralized database to track fraudulent activities, strengthen consumer protection laws, and provide legal solutions for fraud victims. With a comprehensive and coordinated approach, it is expected to reduce fraud cases in online loan services and increase public trust in this industry.